Interconnection Between Religious Studies and Islamic Studies; Theoretical and Practical Approaches - Taufiq, Moh. (Proceedings of International Conference on Muslim Society and Thought, 2024)
Religious studies generally covers various religious traditions around the world, while Islamic studies specifically focuses on Islamic teachings, history, and practices. This research aims to explore the interconnection between religious studies and Islamic studies through theoretical and practical approaches. This research uses a qualitative methodology with literature analysis as the main instrument to understand how these two fields interact and enrich each other. The theoretical approach includes analysis of key concepts in religious studies and Islamic studies, as well as how methodological approaches from these two disciplines can complement each other. The practical approach reviews the implementation of Islamic studies in religious studies programs at various higher education institutions, as well as its impact on cross-cultural understanding and interreligious dialogue. The research results show that the integration of Islamic studies within a religious studies framework not only broadens the scope of academic studies but also enriches theological and ethical discussions in a multicultural and multireligious context. This research concludes that the link between religious studies and Islamic studies offers great potential for the development of a more holistic and inclusive science.